Kepentingan Sejarah, Fungsi, dan Hikmahnya dalam al-Quran - Muhammad Faiz,; Ufies Marizqa Rosyanda,; Zainiah,; M. Ferdi Nur Saputro, (Advances in Humanities and Contemporary Studies, 2022)
History is events that have happened in the past. History in the Qur'an comes directly from Allah. History is said to be a story because history in the Qur'an requires interpretation by the commentators. In Qur'an there are many historical stories that contain a lot of information. The importance of studying history because in it there are events of the Prophet and the previous people who have various functions and wisdom. The historical story in the Qur'an serves as a reassurance, as ibrah (teaching), warning, a source of truth, and an example (uswah). Historical stories in the Qur'an have wisdom including to explain the basis of law and the Shari'a, to justify the Prophet's apostleship, show the miracles of the Qur'an, convince people's hearts of the truth of Islam, and to provide teachings that must be imitated or abandoned from the story contained in the Qur'an.